Improving the quality of SME business operations by applying the concept of organizational learning - Cvjetković Milena; Cvjetković Milovan; Josimović Milica (Ekonomija: teorija i praksa, 2022)
The subject of research in this paper is the concept of organizational learning and the impact it has on improving the quality of business of small and medium enterprises. The aim of the research is to determine how organizational learning should be improved in order for it to give the best possible results in company business operations. The results of the research showed that the efficiency of organizational learning is built on a motivated workforce and team cooperation. Variables of organizational learning have shown the greatest impact on innovative activities and continuous improvements as factors in improving the quality of business. The paper presents a decision-making model with an artificial neural network approach for continuous improvement of the quality of business of small and medium enterprises through the application of the concept of organizational learning. The presented research results can be used as guidelines to owners and managers of small and medium enterprises, indicating the right direction if the aim is to improve the quality of business on the basis of organizational culture that supports the creation and exchange of knowledge.